The wonderful world of communication - Hogben, Lancelot Thomas, 1895- 4 0 16; 5 (Garden City, N.Y : Doubleday, 1969)
Traces the development of man's attempts to preserve and communicate information from prehistoric cave paintings to present day use of machines such as telephones, computers, and television.
Keywords: 2 -- 0; 6; History;Juvenile literature.;History. -- Communication;Communication -- 20; 20; 2